Towards the history of the Vladimir diocese. Bishop Athanasius (Sakharov) and bishop Damian (Voskresensky) (1925–1926) - Kosik Ol'ga (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The published documents characterize the church situation in the Pereslavl’s suﬀragancy of the Vladimir diocese in 1925–1926. They inform about the situation that has been developed in connecting with joining of Pereslavl’s bishop Damian (Voskresensky) to the Provisional higher church council (the Gregorian split). Kovrovsky Bishop Athanasius (Sakharov) has returned to Vladimir from the Zyrjansky exile in February, 1925. He started to govern the Vladimir diocese as the ﬁrst assistant of Vladimir’s archbishop Nikolay (Dobronravov), who was exiled to Moscow. However in May, 1925 the church hierarch, on request of OGPU, had to make the signed statement about the not management of the diocese. In November, 1925 the temporarily governor of the Vladimir diocese had been appointed bishop Damian (Voskresensky). In the middle of December, 1925 the Provisional higher church council (a schismatic institution) has been established by means of OGPU, and bishop Damian was included as the member of the council. After that, bishop Athanasius assumed control of the Vladimir diocese. Metropolitan Sergey (Stragorodsky), the Deputy to the Locum Tenens, condemned the Raskolniks and prohibited their church service. Bishop Damian has soon understood the mistake, repented and was reunited with the Orthodox Church. On January, 15th, 1926 bishop Athanasius was arrested. On March, 15th, 1926, after the prison, the church hierarch of the Vladimir diocese has addressed to bishop Damian. The documents disclose the position of Kovrovsky bishop Athanasius, based on principle, against the church split.